2017
DOI: 10.3233/ves-170604
|View full text |Cite
|
Sign up to set email alerts
|

The vestibular implant: A probe in orbit around the human balance system

Abstract: The primary goal of the vestibular implant is to restore the vestibular function in patients with a disabling bilateral vestibular loss for whom there is currently no available treatment. The prototype developed by our team is a hybrid system consisting of a modified cochlear implant incorporating additional vestibular electrodes. Therefore, in addition of delivering sound information it is also capable of delivering motion information to the central nervous system using electrical stimulation. To date, thirte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 66 publications
2
27
0
Order By: Relevance
“…While beyond the scope of the current paper, recent studies have suggested vestibular implantation as a promising procedure to restore vestibular function in patients with disabling bilateral vestibular deficits . Vestibular implants consist of an array of electrodes that is introduced by an extralabyrinthine or intralabyrinthine surgical approach to electrically stimulating the ampullary nerves .…”
Section: Discussionmentioning
confidence: 99%
“…While beyond the scope of the current paper, recent studies have suggested vestibular implantation as a promising procedure to restore vestibular function in patients with disabling bilateral vestibular deficits . Vestibular implants consist of an array of electrodes that is introduced by an extralabyrinthine or intralabyrinthine surgical approach to electrically stimulating the ampullary nerves .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Perez Fornos et al [29,30] suggest that VOR restoration can improve the stabilization abilities with a VI. Vestibular implants are devices designed to rehabilitate patients suffering from a dysfunction of VOR that impairs gaze stabilization and results in an abnormal loss of visual acuity in dynamic situations.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of SCC afferents has been shown to restore VOR by inducing canal-specific eye movements, with modulation of amplitude or frequency causing a proportional effect on the velocity and direction of the movement [21]. In order to restore bi-directional eye movements using unilateral stimulation, an artificial 'spontaneous' impulse firing rate (as close as possible to the 90 spikes per second firing rate produced in a healthy vestibular system) must be induced in each vestibular nerve [22]. This can then be either up-or downregulated, in response to specific movements to elicit eye movements in different directions [21].…”
Section: Vestibular Implantsmentioning
confidence: 99%